2022
DOI: 10.1002/art.42261
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Zoster Vaccine Uptake and Risk of Flares Among Older Adults With Immune‐Mediated Inflammatory Diseases in the US

Abstract: Objective Persons with immune‐mediated inflammatory diseases (IMIDs) are at an increased risk of herpes zoster (HZ). In 2018, the Centers for Disease Control and Prevention recommended a highly efficacious vaccine, recombinant zoster vaccine (RZV), for prevention of HZ in immunocompetent patients ≥50 years of age. This study was undertaken to estimate RZV vaccination among adults ages ≥50 years with IMIDs during 2018–2019 and to examine possible vaccine‐related flares following RZV. Methods We identified a coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In view of the COVID-19 pandemic and the burden of herpes zoster in patients with lupus,103 the current SLR included a research question regarding the efficacy and safety of vaccines against SARS-CoV-2 and herpes zoster virus (HZV) in lupus. Both the live attenuated and the more efficacious recombinant zoster vaccine have been used in patients with SLE and, although studies are limited, they are considered safe 104 105. Similarly, several observational studies have proven the immunogenicity and safety of SARS-CoV-2 vaccines, which are recommended for patients with SLE 106.…”
Section: Resultsmentioning
confidence: 99%
“…In view of the COVID-19 pandemic and the burden of herpes zoster in patients with lupus,103 the current SLR included a research question regarding the efficacy and safety of vaccines against SARS-CoV-2 and herpes zoster virus (HZV) in lupus. Both the live attenuated and the more efficacious recombinant zoster vaccine have been used in patients with SLE and, although studies are limited, they are considered safe 104 105. Similarly, several observational studies have proven the immunogenicity and safety of SARS-CoV-2 vaccines, which are recommended for patients with SLE 106.…”
Section: Resultsmentioning
confidence: 99%
“…In general populations, various risk factors such as increasing age, female gender, ethnicity of Asia and Oceania, substance abuse such as smoking or alcohol, genetic predisposition, psychological stress, and exposure to immunotoxins can collectively contribute to the elevated susceptibility to herpes zoster ( Thomas and Hall, 2004 ; van Oorschot et al, 2021 ; Curran et al, 2022 ; Kawahira et al, 2023 ). The pre-existing IMIDs themselves are also associated with an increased risk of herpes zoster ( Leung et al, 2022 ), and the use of JAK inhibitors can further increase the risk of herpes zoster in these patients ( Clarke et al, 2021 ). We have reason to believe that the combination of these factors may lead to an even higher incidence of herpes zoster infection.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, there are no prospective trials evaluating the safety and efficacy of the herpes zoster subunit vaccine in SLE patients. However, in a broad retrospective study of patients with autoimmune diseases including SLE, no significant difference in disease flare following herpes zoster subunit vaccine was observed [72 ▪ ]. Other retrospective studies of herpes zoster subunit vaccine that included SLE patients have shown mild flares [73,74].…”
Section: Special Implications Of Zoster Vaccination In Systemic Lupus...mentioning
confidence: 97%